Lateral Opening Wedge Distal Femur Osteotomy and Medial Patellofemoral Ligament Reconstruction for Recurrent Patellar Instability - Thomas E. Moran MD; Adam J. Tagliero MD; Emma Klosterman MD; Pradip Ramamurti MD; Anna E. Sumpter BS; David R. Diduch MD (SAGE Publishing, 2023)
Background: A uniplanar, varus-producing distal femur osteotomy (DFO) may improve patellar tracking by effectively medializing the tibial tubercle, decreasing the Q-angle, and reducing the dislocation vector on the patella. Indications: A 17-year-old female with 8° of genu valgum presented with 18 months of symptomatic left knee patellar instability episodes that limit her function. Technique Description: A lateral subvastus approach to the distal femur was performed. Medial patellofemoral ligament reconstruction (MPFL-R) was conducted up to the point of femoral-sided graft fixation. A lateral opening wedge DFO was made with a sagittal saw and osteotomes, with care taken to maintain the medial cortical hinge. After distraction of the osteotomy site and femoral head allograft wedge placement, the osteotomy was secured with a lateral distal femoral locking plate. Finally, femoral-sided graft fixation for the MPFL-R was completed. Results: There were no immediate complications after surgery. Surgical management led to improvement of the patient's patellar instability, which allowed return to the prior baseline level of function. Discussion/Conclusion: The senior author's preferred technique for a lateral opening wedge DFO in association with an MPFL-R is presented. A varus-producing DFO is a surgical option for patients with genu valgum and recurrent patellar instability who have failed conservative management. This case demonstrates the efficacy of a lateral opening wedge DFO in improving patellar tracking and improving knee function by resolving recurrent patellar instability episodes. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.